Attentional Demand and Cost Responsibility as Stressors in Shopfloor Jobs - Martin, Robin; Wall, Toby D. (Academy of Management Journal, 1989)
Two studies were conducted to test for the effects of attentional demand and cost responsibility on psychological strain. One was a field experiment involving operators of computer-based manufacturing equipment, and the other was a cross-sectional investigation of employees in a wide range of jobs. The results showed increased strain only for those in jobs high on both attentional demand and cost responsibility. Implications for job design for new manufacturing technologies are discussed.